Transcriptomic Analysis of Broussonetia papyrifera Fruit Under Manganese Stress and Mining of Flavonoid Synthesis Genes - Zhiyuan Hu; Yiwang Tang; Jihui Zhang; Taotao Li; Yihan Wang; Yani Huang; Yunlin Zhao; Guiyan Yang; Zhenggang Xu (Plants)
Broussonetia papyrifera is a deciduous tree with significant economic and medicinal value. It demonstrates notable physiological adaptability to mining areas with severe manganese contamination and is a pioneering species in the field of ecological restoration. Flavonoids are vital secondary metabolites that improve plant resilience to environmental stresses. In the study presented herein, immature and mature fruits of B. papyrifera grown in normal and high manganese environments were used as the test materials. B. papyrifera fruit was subjected to transcriptome sequencing via high-throughput sequencing technology to analyze its flavonoid metabolic pathways and related genes. Transcriptome sequencing identified a total of 46,072 unigenes, with an average length of 1248 bp and a percentage of Q30 bases ranging from 92.45 to 93.17%. Furthermore, 31,792 unigenes (69% of the total) were annotated using eight databases, including the GO and KEGG. Analysis of KEGG metabolic pathways and flavonoid content trends in B. papyrifera fruits revealed four unigenes with strong links to the flavonoid biosynthesis pathway under manganese stress: flavone 3-hydroxylase, flavonoids 3′,5′-O-methyltransferase, chalcone synthase, and flavonol synthase. These unigenes may play important roles in regulating flavonoid synthesis in B. papyrifera fruits under manganese stress. This study lays the groundwork for functional gene research in B. papyrifera.